Alexander von Humboldts Weltbild - Knobloch, Eberhard (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2009)
Abstract The paper is divided into five sections. It begins by showing the similarity between Humboldt’s world view and that of the Pythagoreans. It inquires into Humboldt’s notion of nature that comprehends natura naturans and natura naturata as well. Numbers are powers of the univers. They especially occur in the ’only decisive method’ that is in the method of mean values. This method makes it possible to recognize the law guiding the changes of variable quantities. The botanical arithmetic and earth magnetism provide examples. Finally the paper explains how Humboldt combined the three possible approaches to the world that is thinking, acting, and regarding by means of the notion of knowledge. Zusammenfassung Der fünfteilige Aufsatz zeigt zunächst Ähnlichkeiten zwischen Humboldts Weltbild und dem Weltbild der Pythagoreer auf und untersucht Humboldts Naturbegriff, der beides umfasst: Die natura naturans und die natura naturata. Zahlen sind Mächte des Kosmos. Sie treten insbesondere in der ‚einzig entscheidenden Methode‘ auf, der Methode der Mittelwerte. Diese ermöglicht, das Gesetz zu erkennen, das der Änderung variabler Größen zugrunde liegt. Beispiele bieten die Arithmetica botanica und der Erdmagnetismus. Abschließend wird gezeigt, wie Humboldt die drei möglichen Weltzugänge Denken, Handeln, Anschauen im Begriff Wissen miteinander verband.